(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
Understanding the Qur’an is not enough just to read the text raw or in the language we call it textual. Because it is very possible that there is a misinterpretation in understanding the true content of the Qur’an. So it is very important to have research on Asbab an-nuzul with a description approach to the analysis of the Qur’an, namely by looking from the side "when the Qur’an is with it in the environment or place where the Qur’an was revealed". The aim is to gain haqiqi error in interpreting what is contained in the Qur’an. This study will discuss how important asbabun nuzul is in interpreting the Qur’an so that someone is not mistaken in interpreting the Qur’an. The results of this study found that Asbab an-nuzul has a very important role in getting the truth when interpreting the Qur’an, where to understand a truth in the Qur’an, a mufassir needs tools, one of which is by looking at the events when the verse was revealed, the existence of a verse of the Qur’an cannot be separated from an existing event and must have a number of existing problems, and should be known in detail. As religious people who are obedient and from an early age have embedded the values of tawhid, it is mandatory for us to believe in the revelation of Allah that has been revealed to the Prophet Muhammad SAW, has been maintained authenticity by Allah SWT